(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The Madura ethnic group in Indonesia has a robust migration heritage. The presence of Madura enterprises is readily identifiable in numerous locations, particularly in major Indonesian cities and most metropolitan regions of Java. They typically participate in many economic activities commonly categorized as the informal sector. The success of a firm is determined not just by economic variables but also by social, cultural, and religious elements. The primary objective of every business stakeholder is to attain success. Key aspects contributing to the success of the 24-hour Madura stall enterprise encompass human capital, work ethic, entrepreneurial motivation, and the religious beliefs maintained by the business owners. This research is crucial for elucidating the interactions among these four criteria and their contribution to corporate success. This study employed a quantitative methodology to comprehend the linkage between variables. The population comprises 24-hour Madura stall entrepreneurs located in Malang, Surabaya, Jember, and other cities of East Java. The sample was determined using a purposive sampling technique and it was selected proportionally from each city that fulfilled the specified requirements. The researcher distributed 360 questionnaires directly to respondents in those research areas and returned 335 responses. Concurrently, individuals in other prominent cities on the island of Java were disseminated online via Google Forms. The findings indicated that entrepreneurial motivation is affected by Islamic religious values, the Madurese work ethic, and human capital. Business success is strongly affected byMadurese work ethic and entrepreneurial desire instead of Islamic religious ideals or human capital. Furthermore, entrepreneurial motivation acts as a full mediator for the impact of Islamic religious values and human capital on business success, and as a partial mediator for the effect of the Madurese work ethic on business success.